An attempt to locate the Russian spatial planning system within the European planning families. (April 2023) - Živanović, Zora; Tošić, Branka; Berisha, Erblin; Perić, Ana
Abstract: Since the end of the 1980s, several studies have been conducted aiming at understanding the heterogeneity of spatial planning traditions across Europe. Over the years, such studies became more comprehensive and included many European (and not only the European Union) countries. Nevertheless, some parts of Europe (e.g., the Western Balkans or the post-Soviet countries) usually remained excluded from the mentioned studies. To mitigate this gap, the paper focuses on the case of Russia. Using a twofold methodological approach, the paper firstly examines the attributes of Russian spatial planning (through a multi-layered analysis of the socio-economic and institutional settings, the evolution of spatial planning over a century, and contemporary planning instruments and procedures of plan-making), to then compare the attributes of the Russian spatial planning system to the core features of the European planning styles. As a result, the elements of multiple distinct spatial planning styles can be traced in Russian spatial planning: land use management and regional economic planning seem to prevail, whilst comprehensive integrated and urbanism traditions are less represented but not absent. Bearing in mind the complexity of the exercise, this contribution should be considered a preliminary attempt to enlarge the existing comparative studies beyond European countries. Highlights: The paper examines the characteristics of Russian spatial planning. The authors have compared the Russian spatial planning system to the features of the European planning styles. During the Cold-War period, 1990s, spatial development in Russia became rather chaotic and unsustainable. The authors have concluded that land use and regional economic planning seem to prevail in the planning system of Russia. The paper is an attempt to enlarge the comparative studies in relation to planning systems beyond European countries.